High-resolution spatio-temporal characteristics of urban evapotranspiration measured by unmanned aerial vehicle and infrared remote sensing. (15th August 2022) - Qin, Longjun; Yan, Chunhua; Yu, Leiyu; Chai, Minwei; Wang, Bei; Hayat, Muhammad; Shi, Zhe; Gao, Huihui; Jiang, Xianchenghao; Xiong, Bowen; Mao, Peng; Qiu, Guo Yu
Abstract: Evapotranspiration (ET) cooling of urban spaces is an effective and economical way to improve the urban thermal environment. However, the distribution of urban ET rate is typically unknown owing to the high heterogeneity of urban land covers, which limits the application of many conventional techniques for measuring ET, such as ground-based observations and satellite remote sensing. In this study, an improved approach called "UAV + IRs + 3T", combining unmanned aerial vehicle (UAV), thermal infrared remote sensing, and a three-temperature model (3T), was developed for estimating urban ET and validated by Bowen ratio method. Results showed that the proposed method could accurately measure urban LE with R 2 = 0.95, MAE = 21.98 W m −2, RMSE = 30.33 W m −2, RRMSE = 19.65%. The proposed method could obtain urban ET with an ultra-high spatial resolution (approximately 15.5 cm) and temporal resolution (once per hour). Furthermore, 9 plant species distributed across the 18 sample plots showed significant differences in mean intra-day ET rates. Even for the same plant species at different sites, such as Ficus concinna and Zoysia matrella, their average intra-day ET rates differed by 50% and 400%, respectively. These large differences could be attributed to artificial pavement and infrastructure, different artificial irrigation methods, and difference in artificial and natural shade. In conclusion, there is spatio-temporal variability in urban ET rates, which can be precisely revealed by the proposed method. Therefore, the "UAV + IRs + 3T" method has the potential for a wide range of applications in urban environmental planning. Highlights: Propose a new method based on UAV and infrared RS for observing urban evapotranspiration. The new method could obtain urban ET with an ultra-high spatio-temporal resolution. Different pavement, infrastructure, irrigation and shade causes different urban ET. Average intra-day ET of the same plant species differ up to 400% at different sites.